2010
DOI: 10.1007/s11270-010-0605-8
|View full text |Cite
|
Sign up to set email alerts
|

Levels of 131I and Six Natural Radionuclides in Sludge from the Sewage Treatment Plant of Valladolid, Spain

Abstract: The levels of 131 I and six natural radionuclides ( 238 U, 226 Ra, 210 Pb, 228 Ra, 224 Ra, and 40 K) were determined in sewage sludge samples obtained from an urban wastewater treatment plant that services a medium-sized town in Spain. Secondary treatment of wastewater consisting of anaerobic, anoxic, and oxic stages is collectively called A2O processing. Radio analytical determinations were performed by gamma spectrometry using a highpurity germanium detector. This technique has proven useful in identifying l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
10
0
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 21 publications
(19 citation statements)
references
References 10 publications
2
10
0
1
Order By: Relevance
“…The highest 131 I concentration in sewage sludge collected from the Stony Brook WPCP (148 Bq g j1 ) exceeds the previously published maximum value by more than four times (31 Bq g j1 , ISCORS 2003). Specific activities of 131 I in sewage sludge reported in other studies are generally lower than these values (0.004Y2.5 Bq g j1 dry weight, Erlandsson and Mattsson 1978;Erlandsson et al 1983;Barci-Funel et al 1993;Brennan 1997;Dalmasso et al 1997;Puhakainen 1998;Punt et al 2007;Chang et al 2011;Jiménez et al 2011). It is possible that the unique conditions (i.e., a small plant serving a regional thyroid cancer treatment facility) cause the Stony Brook WPCP to have the highest specific activities of 131 I in sewage sludge relative to other facilities.…”
Section: Resultsmentioning
confidence: 86%
See 2 more Smart Citations
“…The highest 131 I concentration in sewage sludge collected from the Stony Brook WPCP (148 Bq g j1 ) exceeds the previously published maximum value by more than four times (31 Bq g j1 , ISCORS 2003). Specific activities of 131 I in sewage sludge reported in other studies are generally lower than these values (0.004Y2.5 Bq g j1 dry weight, Erlandsson and Mattsson 1978;Erlandsson et al 1983;Barci-Funel et al 1993;Brennan 1997;Dalmasso et al 1997;Puhakainen 1998;Punt et al 2007;Chang et al 2011;Jiménez et al 2011). It is possible that the unique conditions (i.e., a small plant serving a regional thyroid cancer treatment facility) cause the Stony Brook WPCP to have the highest specific activities of 131 I in sewage sludge relative to other facilities.…”
Section: Resultsmentioning
confidence: 86%
“…Other studies have reported 131 I concentrations in sewage sludge between 0.004Y2.5 Bq g j1 dry weight (Erlandsson and Mattsson 1978;Erlandsson et al 1983;Barci-Funel et al 1993;Brennan 1997;Dalmasso et al 1997;Puhakainen 1998;Punt et al 2007;Chang et al 2011;Jiménez et al 2011). The Interagency Steering Committee on Radiation Standards (ISCORS) published the most comprehensive survey of radioactivity in sewage sludge.…”
Section: Iodine-131 Concentrations In Sewage Sludgementioning
confidence: 99%
See 1 more Smart Citation
“…In the case of 210 Pb, there is more literature as more studies focusing on the determination of radionuclides of natural origin have been reported (ISCORS, 2003;Kleinschmidt and Akber, 2008;Jiménez et al, 2011). Jiménez et al (2011) analyzed sludge samples from a urban sewage treatment plant located in Valladolid (Spain), where there are only local pollution influences.…”
mentioning
confidence: 99%
“…Jiménez et al (2011) analyzed sludge samples from a urban sewage treatment plant located in Valladolid (Spain), where there are only local pollution influences. This work reported 210 Pb concentrations in 21 sludge samples ranging between 25 Bq kg À 1 and 69 Bq kg À 1 and these 210 Pb activities levels are similar to the values obtained in our study.…”
mentioning
confidence: 99%